2020
DOI: 10.1007/s12264-020-00468-9
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Brain Monosynaptic Inputs to Hypoglossal Motor Neurons in Mice

Abstract: Hypoglossal motor neurons (HMNs) innervate tongue muscles and play key roles in a variety of physiological functions, including swallowing, mastication, suckling, vocalization, and respiration. Dysfunction of HMNs is associated with several diseases, such as obstructive sleep apnea (OSA) and sudden infant death syndrome. OSA is a serious breathing disorder associated with the activity of HMNs during different sleep-wake states. Identifying the neural mechanisms by which the statedependent activities of HMNs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…In our study, we left the PB CGRP to the CEAc pathway untouched, as the PSTN is connected to the CEAm and caudal SI. Therefore, we impacted the network downstream from the CEAc, indicating either that damaging the network at any level diminishes the anorexic response associated with sickness or that an intact PSTN/CbN is necessary to relay the CEA information processing and anxietyrelated signals to downstream centers (59,60) or back to the telencephalon through the thalamus (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we left the PB CGRP to the CEAc pathway untouched, as the PSTN is connected to the CEAm and caudal SI. Therefore, we impacted the network downstream from the CEAc, indicating either that damaging the network at any level diminishes the anorexic response associated with sickness or that an intact PSTN/CbN is necessary to relay the CEA information processing and anxietyrelated signals to downstream centers (59,60) or back to the telencephalon through the thalamus (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Two kinds of PRV carrying different fluorescent proteins were injected into different parts of the experimental animals, followed by detection of expressions and distributions of fluorescent proteins in certain brain regions after days of virus infection. Neurons labeled by two kinds of fluorescent proteins indicated that the brain area where labeled neurons distributed was involved in the regulation of two different injection sites [82,83]. For example, in our study, PRV531 (GFP) and PRV724 (mRFP) were injected into the heart and small intestine of C57 BL/6J mice, respectively.…”
Section: Two Kinds Of Neurotropic Virus Labeled Neuronsmentioning
confidence: 65%
“…The suppression hypoglossal nerve activity causes diminished genioglossus protrusion and retraction during inspiration (Fuller et al ., 1999; Gestreau et al ., 2005, Lee et al ., 2012). Together, these findings suggest that the pre-BötC contains a critical pool of pre-motor neurons that project to hypoglossal and vagal motor neurons (Guo et al ., 2020; Menuet et al ., 2020), which have an essential function in the dynamic regulation of upper airway patency. Thus, the present study further extends the role of the pre-BötC from its established role as the inspiratory rhythm generator (Feldman & Del Negro 2006; Feldman et al ., 2008; Del Negro et al ., 2018) to the dynamic regulation of upper airway patency and is also consistent with its recently identified role in the mediation of cough (Shen et al, 2022) that specifically requires post-inspiratory laryngeal constriction to generate high velocity expiratory airflow (see Dutschmann et al, 2014).…”
Section: Discussionmentioning
confidence: 92%